2022
DOI: 10.3390/ijerph191912826
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Mental Health, Lifestyle Factors and Worries about Climate Change in Norwegian Adolescents

Abstract: Climate change is a serious global health threat that has an impact on young people’s lives and may influence their mental health. Since the global climate strike movement, many adolescents have expressed worries about climate change. Thus, the aim of this study is to examine the prevalence of worries about climate change, and factors associated with worries about climate change, in a representative sample of Norwegian adolescents. Data were retrieved from Ungdata, an annual nationwide online youth survey. Ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 42 publications
(64 reference statements)
4
28
0
Order By: Relevance
“…Nevertheless, recent studies indicate that an increased salience of death due to the COVID-19 pandemic would also be associated with an increase in the level of depressive symptoms, which was not the case in the present study ( 73 75 ). Additionally, Russia's invasion of Ukraine, which started in February 2022, the recent energy crisis, economic changes, rising inflation rates, climate change and related worry in youths and adolescents ( 76 78 ) could, to some extent, contribute to an explanation of this specific increase in only suicidal ideation, but further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent studies indicate that an increased salience of death due to the COVID-19 pandemic would also be associated with an increase in the level of depressive symptoms, which was not the case in the present study ( 73 75 ). Additionally, Russia's invasion of Ukraine, which started in February 2022, the recent energy crisis, economic changes, rising inflation rates, climate change and related worry in youths and adolescents ( 76 78 ) could, to some extent, contribute to an explanation of this specific increase in only suicidal ideation, but further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In a Norwegian study of people aged 13-19 years, Leonhardt at al. found that those aged 15-16 years were more likely to be worried about climate change, but the relationship with age was non-linear, decreasing among those aged 18-19 years [21]. In a qualitative study by Chou et al, the authors noted that children aged around 11-12 years may experience more climate-related distress compared to younger children as they develop and become more able to envisage a hypothetical future [14].…”
Section: Resultsmentioning
confidence: 99%
“…Studies often suggested that females express higher eco-anxiety levels than males, but few empirically tested for potential gender differences. Leonhardt et al found that young women were more likely to experience eco-anxiety than men, 14% of females reported being very worried compared to 7% of males, and 28% of males reported being not worried at all, compared to 10% of females [21]. In their logistic regression models adjusted for sociodemographic factors and leisure activities, females had 2.60 (95% CI: 2.53–2.67) higher odds of eco-anxiety compared to males, and this association persisted after further adjustment for mental health and substance use (cannabis and alcohol).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations